Value co-creation and customer satisfaction mediation on the service innovation and generation Z consumers’ repurchase intention in Vietnam - Quang Phu Tran; Anh Duc Do; Dieu Linh Ha; Phuong Thao Bui; Duc Kien Nguyen; Nguyen Hoang Dung Tran (Cogent Business & Management)
This study aims to investigate the association between service innovation (supportive service innovation and interactive service innovation) and the repurchase intention of Generation Z customers in Vietnam. Specifically, it examines the mediation roles of value co-creation and customer satisfaction in the connection between service innovation and consumers’ repurchase intention. The conceptual model was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the SmartPLS 4 software based on data from 1393 samples validity of Generation Z customers in Vietnam with diverse demographic characteristics in terms of gender, educational level and place. Simultaneously, the study discovered the existence of differences in repurchase intention among customers with different demographic characteristics. The results of this study indicate the service innovation and interactive service innovations influence each other and affect Generation Z customers’ repurchase intention. Specifically, the mediation analysis results confirm that value co-creation acts as a full mediator in the relationship between service innovation and repurchase intention. The findings provide theoretical and practical contributions to enhance Generation Z customers’ repurchase intention through service innovation, value co-creation, and satisfaction.